Assessment of Bukola Saraki Administration in Kwara State of Nigeria (2003-2011) - Yemi Daniel Ogundare (Universitas Jember, 2022)
Abstract The paper examines the assessment of the Bukola Saraki Administration 2003-2011. The administration is an act of getting things achieved through the people; it requires leadership quality, ideology, and value. The historical analysis of Kwara State administrations in the fourth republic is not complete without considering the political dynastic transfer of Olusola Saraki to a biological son Bukola Saraki in the political process of Kwara State as a governor. The objective of this paper is to assess the success and failure of the Peoples Democratic Party (PDP) in Kwara State during the Abubakar Bukola Saraki administrations. The theory employed in this paper is the Stakeholders theory, which is relevant to this work. The research methodology is a secondary source and analytical. The findings of the paper identify the successes and limitations of PDP administrations from 2003-2011. The paper recommends democratic lifestyle leadership with transparency and accountability government to the citizen as the best set of administration to be practiced in any polity.